2007
DOI: 10.1021/ja076641c
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Shows Preference for the Interior of Polyunsaturated Lipid Membranes

Abstract: Recent neutron scattering experiments showed a striking manifestation of the aversion between polyunsaturated fatty acid (PUFA)-containing lipids and cholesterol. Selectively deuterated cholesterol/ 1,2-diarachidonylphosphatidylcholine (DAPC) samples revealed that the hydroxyl of the sterol resides at the center of the bilayer. Here we use a recently parametrized coarse grain simulation model to shed light on these puzzling experimental observations. Using a simulation setup in close correspondence to the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
190
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 195 publications
(221 citation statements)
references
References 11 publications
29
190
2
Order By: Relevance
“…5 The fact that cholesterol contains only a single polar group makes it more hydrophobic than a phospholipid; the calculated free energy of partition for a cholesterol monomer between water and hydrocarbon is comparable to that of an alcohol of C20 chain length [16]. As a consequence, although most cholesterol molecules in a membrane are located with their -OH groups in the headgroup region of the lipid bilayer with their hydrophobic ring systems more or less perpendicular to the plane of the membrane [1], a proportion of the cholesterol molecules occupy positions with their -OH groups deep within the fatty acyl chain region of the bilayer, close to the bilayer centre, as shown by neutron diffraction studies and full atomistic and coarse-grained molecular dynamic simulations and consistent with the reported high rate of flip-flop of cholesterol across the membrane [17][18][19][20].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…5 The fact that cholesterol contains only a single polar group makes it more hydrophobic than a phospholipid; the calculated free energy of partition for a cholesterol monomer between water and hydrocarbon is comparable to that of an alcohol of C20 chain length [16]. As a consequence, although most cholesterol molecules in a membrane are located with their -OH groups in the headgroup region of the lipid bilayer with their hydrophobic ring systems more or less perpendicular to the plane of the membrane [1], a proportion of the cholesterol molecules occupy positions with their -OH groups deep within the fatty acyl chain region of the bilayer, close to the bilayer centre, as shown by neutron diffraction studies and full atomistic and coarse-grained molecular dynamic simulations and consistent with the reported high rate of flip-flop of cholesterol across the membrane [17][18][19][20].…”
Section: Introductionsupporting
confidence: 75%
“…The ratio of the number of deep cholesterol molecules not in contact with protein to the total number of cholesterol molecules is 0.023 in the presence of the β 2 -adrenergic receptor and 0.028 in the presence of the A 2A adenosine receptor (Table S1). Marrink et al [18] reported values between 0.03 and 0.1 for the proportion of deep cholesterol molecules in lipid bilayers in the absence of protein, the value depending on the degree of unsaturation of the lipid fatty acyl chains.…”
Section: Deep Cholesterol Binding Sites On Agonist-free and Agonist-bmentioning
confidence: 99%
“…Over the years, this technique of isotopic substitution has been used to study viruses (Jacrot, 1976;Cusak et al, 1985), proteins (Satre and Zaccai, 1979;Zaccai, 2000a,b), DNA/RNA structure (Parfait et al, 1978;Hammermann et al, 1998;Ledere et al, 2005), and model membranes (Zaccai et al, 1975Büldt et al, 1978;Léonard et al, 2001). An example where isotopic substitution was used, and that has attracted some attention, is the bilayer system made up of lipids with polyunsaturated fatty acid (PUFA) chains (20:4-20:4) and the location of cholesterol therein (Harroun et al, 2006Marrink et al, 2008) -some of the earliest diffraction studies of cholesterol in lipid bilayers are the pioneering works of Franks (1976), and Worcester and Franks (1976).…”
Section: Isotopic Substitution In Neutron Scattering Studiesmentioning
confidence: 99%
“…The experimental data by Harroun et al (2006Harroun et al ( , 2008 were revisited by Marrink et al (2008) using the MARTINI coarse grained (CG) model to simulate the behavior of cholesterol in different lipid bilayers. The MARTINI model groups atoms into CG beads allowing for simulation times in the microsecond range, while practically retaining atomic resolution detail.…”
Section: Isotopic Substitution In Neutron Scattering Studiesmentioning
confidence: 99%
“…Sterols have been observed to translocate without pores [57,58]. On the other hand, sterols are known to translocate at much larger rates compared to many other lipids, the timescales ranging over seconds rather than hours, which may explain why transient pores are not crucial for their translocation processes.…”
Section: Flip-flops Of Lipid Molecules Across Protein-free Lipid Membmentioning
confidence: 99%